2019
DOI: 10.1029/2018jb016536
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrates in Permafrost: Distinctive Effect of Gas Hydrates and Ice on the Geomechanical Properties of Simulated Hydrate‐Bearing Permafrost Sediments

Abstract: The geomechanical stability of the permafrost formations containing gas hydrates in the Arctic is extremely vulnerable to global warming and the drilling of wells for oil and gas exploration purposes. In this work the effect of gas hydrate and ice on the geomechanical properties of sediments was compared by triaxial compression tests for typical sediment conditions: unfrozen hydrate‐free sediments at 0.3 °C, hydrate‐free sediments frozen at −10 °C, unfrozen sediments containing about 22 vol% methane hydrate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…However, it should be noted that the shedded hydrates will not enter the pores immediately to accomplish filling but instead will support the sand particles near the original position. The retention of hydrates between the sand particles hinders the rearrangement of the sand particles during shearing, and the sand particles have to climb over the adjacent sand particles to attain rearrangement, which could result in dilatancy in the hydrate‐bearing specimen (Choi et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that the shedded hydrates will not enter the pores immediately to accomplish filling but instead will support the sand particles near the original position. The retention of hydrates between the sand particles hinders the rearrangement of the sand particles during shearing, and the sand particles have to climb over the adjacent sand particles to attain rearrangement, which could result in dilatancy in the hydrate‐bearing specimen (Choi et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Natural gas hydrates (NGHs) are ice-like compounds consisting of methane molecules within a water framework (Englezos, 1993), which is stable under high-pressure and low-temperature conditions, typically naturally occurring in submarine continental margins, permafrost, and Arctic regions (Koh et al, 2012;Yang et al, 2019). The gross NGH reserves are estimated to be 1-150×10 15 m 3 (Boswell & Collett, 2011;Lee & Holder, 2001;Makogon et al, 2007), which are twice as much as all known conventional fossil fuels and more than 10 times the total reserve of conventional natural gas resources on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the specimen void ratio has increased to a certain extent, some sand particles have to roll over the adjacent sand particles with continued axial loading. And hydrate would encapsulate the sand particle surface forming large‐scale cementation structures (Yang et al, 2019), as shown in Figure 14, making sand particles rearrangement more difficult to accommodate the axial loading. As a result, a failure pattern with a clear shear band has been formed rather than drum‐like failure patterns.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, hydrate, gas, water, and ice saturation were calculated as shown in Table 1. The same formulation as our previous work 35 was used for the calculation of the saturation. For purging the remaining methane gas and reducing the proportion of remaining free methane in the gas phase without dissociation of methane hydrate, flue gas composed of 85.4 mol % N 2 and 14.6 mol % CO 2 was injected to the cell at a pressure approximately 10 times the equilibrium pressure of methane hydrate at the target temperature after hydrate formation.…”
Section: Methodsmentioning
confidence: 99%